Dual Frequency Microstrip Antenna Fed by Electromagnetic Coupling For Satellite Application - Indra Surjati Surjati; Yuli Kurnia Ningsih; Benny Reinmart (UIN Sultan Syarif Kasim Riau, 2011)
Recently, the most popular technique for obtaining dual frequency operation is by introducing a reactive loading to a single patch antenna. This paper proposed a design of dual frequency operation microstrip antenna without using a reactive loading to a single patch antenna. The proposed antenna fed by microstrip feed line and the two resonant frequencies can be generated by controlling the length of the patch antenna and also by adjusting the position and the length of the microstrip feed line. The proposed antenna was designed to be able to work on two different frequencies for Satellite apllication which is at 3.702 GHz up to 4.198 GHz for downlink frequency and at 5.927 GHz up to 6.423 GHz for uplink frequency. The results shown that the first frequency is at 3.9 GHz with return loss of -27.84 dB, VSWR 1.085 and impedance bandwidth 416 MHz or about 83.8%. The second frequency is at 6 GHz with return loss of -18.43 dB, VSWR 1.272 and impedance bandwidth 385 MHz or about 77.6%.Keywords: Dual frequency, rectangular microstrip antenna, electromagnetic coupling, satellite.